On interlingual equivalence in the context of contrastive phraseology and phraseotranslation - Sułkowska, Monika (Papers in Linguistics, 2021)
The aim of the article is to analyze the concept of interlinguistic equivalence from the perspective of an expert in phraseology. In the first part, the author analyzes the concept of equivalence based on the research conducted over the years. The article discusses various typologies of this phenomenon, as well as its importance for contrastive research and for translation studies. In the second part of the text, the author presents the notion of a phraseological unit and interlinguistic equivalence within the field of contrastive phraseology. The third part of the article deals with the issues of phraseotranslation and describes the problem of interlinguistic equivalence from the perspective of translation of broadly understood phraseology.